The politics of the page: cutting and pasting in South African and African-American newspapers. (2nd January 2019) - Hofmeyr, Isabel; Peterson, Derek R.
ABSTRACT: In this essay – which frames this special issue of Social Dynamics – we focus on the "exchange system, " by which newspaper editors mutually consented to reprint material from each other. The work of clipping, citation, condensation and republication were a creative part of the working pattern in late-nineteenth and early-twentieth-century newsrooms. The exchange system furnished editors and authors with transnational resources by which to experiment with new voices and new forms of address. Newspapers were collages, pasted together by editors who vacuumed material out of a circulating print commons, assembled clippings on the page, and brought it all to print. After publication newspapers were disassembled, clipped, recopied, and archived. The essays collected here show publication to be a springboard by which some compositions vaulted into new domains. Readers clipped newspapers apart and reassembled them in scrapbooks, in folders, and in archives. By this downcycling they refashioned texts as emblems of solidarity, as signifiers of commitments, and as proof of purpose. Our purpose here is to deaccession newspapers, unglue the bits of paper pasted onto the page, and trace the looping passage of texts into and out of print.